2013
DOI: 10.1007/s00280-013-2104-2
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and tissue distribution of larotaxel in rats: comparison of larotaxel-loaded microsphere with larotaxel-solution

Abstract: These results suggest that lipid microsphere could be an effective parenteral carrier for LTX delivery in cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…In addition, a dose correlation study suggested that the AUC was dose proportional within the experimental doses, although there is a trend towards reduced clearance as the dose increases. Also, there was no significant difference in half‐time (p > 0.05) at three dose levels, further indicating the linear pharmacokinetics of TM‐2 within the experimental doses, which is consistent with other taxanes …”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…In addition, a dose correlation study suggested that the AUC was dose proportional within the experimental doses, although there is a trend towards reduced clearance as the dose increases. Also, there was no significant difference in half‐time (p > 0.05) at three dose levels, further indicating the linear pharmacokinetics of TM‐2 within the experimental doses, which is consistent with other taxanes …”
Section: Resultssupporting
confidence: 77%
“…A rapid initial‐phase half‐life was averaging 4 min followed by an intermediate‐phase half‐life of around 1 h, and then a prolonged terminal‐phase half‐life averaging 6 h was observed. Compared with larotaxel administrated to rats (4 mg/kg), TM‐2 has a lower C max and AUC, a higher plasma clearance, a larger apparent volume of distribution and a longer elimination half‐life . But TM‐2 exhibits similar AUC, C max and plasma clearance to docetaxel (5 mg/kg), although a larger apparent volume of distribution and a longer elimination half‐life was observed .…”
Section: Resultsmentioning
confidence: 92%
“…Comparing the tissue distribution of lipid microspheres with that of a solution might explain this. As reported , in contrast to the concentration in the plasma, the larotaxel concentration of lipid microspheres in most tissues was lower that that of a solution formed by adding polysorbate 80. It is believed that CTX could penetrate into tissues faster in solution rather than in lipid microspheres, which resulted in an increased AUC for CTX‐LM.…”
Section: Resultsmentioning
confidence: 54%
“…A total of 12 rats were randomly divided into two groups, with six in each (Li et al, 2011;Liu et al, 2013). The animal number was calculated based on the power analysis with a power of larger than 80% in the pre-experiment.…”
Section: Pharmacokinetic Study Of Ltx Solution and Modified Liposomesmentioning
confidence: 99%
“…The animal number was calculated based on the power analysis with a power of larger than 80% in the pre-experiment. Group 1 was randomly selected and treated with LTX solution at a dose of 4 mg kg À1 (1 ml of the injection at the concentration 1.0 mg ml À1 of LTX was administered via the tail vein), while a corresponding dose of LTX-loaded liposomes were administered to Group 2 (Kurata et al, 2000;Liu et al, 2013;Robert et al, 2010;Sessa et al, 2002;Yamamoto et al, 2009). Blood samples of about 0.3 ml were collected from the suborbital vein into heparinised centrifuge tubes, at 0.083, 0.167, 0.333, 0.5, 1, 2, 3, 4, 6, 8 and 12 h after dosing.…”
Section: Pharmacokinetic Study Of Ltx Solution and Modified Liposomesmentioning
confidence: 99%